BIM - Modeling of transport infrastructure objects - Shamraeva, Victoria (E-business technologies conference proceedings, 2021)
The article analyzes the geographic information system (GIS) of the Avtodor state company (developer "Indor-Soft", Tomsk). The implementation of the project through BIM modeling is described, on the example of construction of transport infrastructure facilities of the Far Western bypass of Krasnodar project (FWBK). Issues of standardization and database creation of information models in urban planning and road construction are currently priority areas in the Russian Federation. Evidence-based reasoning is given that it is optimal to use GIS at the operational stage of a complete BIM model of the road. Are revealed the main functionality and examples of using of the Avtodor state company IndorRoad GIS for data entry, accounting and analysis, to solve practical problems of road maintenance.